Antifungal Activity of Endophytic Bacteria Isolated from Miana Plants (Coleus scutellarioides (L.) Benth.) against Candida albicans - Yunita, Melda; Lumbantobing, Ruth Magdalena; Tahitu, Ritha (Folia Medica Indonesiana, 2023)
Highlights: 1.Due to the adverse effects associated with current antifungal drugs, research on traditional medicine is necessary to explore other options for candidiasis treatment. 2.Following the findings of this study, it is recommended to conduct further research by incorporating Coleus scuttellarioides filtrate into the growth medium, since this may improve bacterial growth by producing optimal secondary metabolites. Abstract Candida albicans is the most common organism responsible for both mucosal and systemic infections, accounting for approximately 70% of fungal infections worldwide. Miana, scientifically known as Coleus scuttellarioides (L.) Benth., is recognized for its use in traditional medicinal practices. Miana plants contain endophytic bacteria that possess the ability to produce secondary metabolites with potential antifungal agents. The objective of this study was to assess the antifungal activity of nine endophytic bacteria isolates derived from Coleus scuttellarioides against Candida albicans. This study was laboratory-based qualitative experimental research that applied the Kirby-Bauer diffusion method and several modifications. The Candida albicans specimens were spread throughout the entire potato dextrose agar medium. Afterwards, paper discs that had been soaked in a liquid culture of endophytic bacterial isolates were carefully placed on the surface of the medium. The complete setup was then incubated for 1–2 days. The potential antifungal activity of endophytic bacteria was assessed by observing the emergence of a clear zone surrounding their growth, which would indicate inhibition. An additional observation was performed in the follow-up test, involving the use of Sabouraud dextrose agar medium to confirm the initial test result. The results from the inhibitory test revealed that none of the bacterial isolates exhibited any inhibition zone. Conversely, ketoconazole as the positive control showed an inhibition zone with an average diameter of 28.5 mm. In conclusion, endophytic bacterial isolates obtained from Coleus scuttellarioides have no discernible antifungal properties against Candida albicans. This study implies that ketoconazole remains effective in treating infections caused by Candida albicans.